POLA KOMUNIKASI KOMUNITAS PENGGEMAR FOTOGRAFI SAMARINDA MEDIA SPORT (SMS) DALAM MEMBANGUN CITRA KOMUNITAS - Randy Surya Putra; Rina Juwita (Lafadz Jaya Publisher, 2023)
Community is basically a gathering place for individuals who have the same interest and passion for something. A community can also be formed from a medium that we can call photography. A photo can contain various meanings and information in it. Samarinda Media Sport (SMS) is one of the forums that handles sports photography activists and was formed in 2022. The research conducted is descriptive qualitative in nature. The data sources used are primary data and secondary data. Primary data through video/audio recording and taking photos. Recording of main data sources through interviews or observations. Secondary data by taking data from the Management of Samarinda Media Sport and other reference books. Data collection techniques are using interviews or interviews. Data analysis uses the Miles & Huberman model. The results of the research on communication patterns helped build the Samarinda Media Sport community in the process of labeling the internal community which can shape people's perceptions of the company as a program that has a positive impact on society and also builds community image. Supporting factors in building the community's image are family membership which creates harmony among fellow community members, transparency which makes members comfortable being in this community and opening wide doors for anyone who wants to learn related to sports photographers.